1987
DOI: 10.1530/jrf.0.0810617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryptorchidism on steroidogenic and mitogenic activities in rat testicular interstitial fluid

Abstract: Summary. There was a significant (P < 0\m=.\05) and consistent increase in the potency of steroidogenic stimulatory activity (testosterone production by purified Leydig cells in vitro) in testicular interstitial fluid of the cryptorchid compared to the scrotal testis from 1 to 4 weeks after the induction of unilateral cryptorchidism. In contrast, the level of mitogenic activity ([3H]thymidine incorporation into 3T3 cells) was not significantly different between interstitial fluid from cryptorchid and scrotal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Consistent with previous observations, peripheral testosterone levels were effectively normal in the bilaterally cryptorchid rats, as indicated by the seminal vesicle and thymus weights [40,41]. Testicular IF testosterone levels also appeared to be either normal or slightly elevated in the cryptorchid rat.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous observations, peripheral testosterone levels were effectively normal in the bilaterally cryptorchid rats, as indicated by the seminal vesicle and thymus weights [40,41]. Testicular IF testosterone levels also appeared to be either normal or slightly elevated in the cryptorchid rat.…”
Section: Discussionsupporting
confidence: 90%
“…Testicular IF testosterone levels also appeared to be either normal or slightly elevated in the cryptorchid rat. Although similar results have been reported elsewhere [40,42], this latter observation was analyzed further because it was not consistent with previous results obtained in our laboratory and in some other laboratories using the same experimental model [41,43,44]. Continued synthesis of testosterone after testis collection, leading to artificially elevated testosterone levels in testicular IF, has been raised previously as a potential technical problem [45,46].…”
Section: Discussionmentioning
confidence: 52%
“…Interstitial fluid (IF) collected from adult rats clearly contains mitogenic activity (Drummond et al, 1988;Risbridger et al, 1987;Ojeifo et al, 1990), but this activity is unchanged in the first 2 weeks after EDS treatment (when proliferation of LC precursors is occurring [see above]) or after experimental cryptorchidism (when LC hypertrophy is occurring, see above). Presumably, the mitogen present in adult testicular IF is different from that which exerts the effects just described during puberty, although no studies of mitogenic activity in IF collected from immature rats have been reported.…”
Section: Role Of Paracrine Factors In Lc Tumorigenesismentioning
confidence: 99%
“…Both changes can be averted by exogenous epidermal growth factor supplementation [26]. As a result of the diversity of putative growth factors and the difficulty in obtaining fractionated germ cells for culture, a number of groups have continued to utilize the mouse 3T3 fibroblast system in an easily performed bioassay that can distinguish differences in testicular mitogenic activity in a number of physiologic states, including vitamin A deficiency [28] and cryptorchidism [22].…”
Section: Discussionmentioning
confidence: 99%